Water Budget Estimation in Bellary Region - Jayaram, N S; Ramamath, B; Verma, B (Annals of Arid Zone, 2016)
The water budget has been worked out for the Beliary Region based on computation of Potential evapotranspiration by Penman's equation for the cropping years 1957-58 to 1967-68. The mean Potential evapo-transpiration and the precipitation respectively are 186.34 and 49.42 centimeters thus showing a total deficit of 136.92 centimeters.